2017
DOI: 10.1037/bul0000092
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and thematic semantic systems.

Abstract: Object concepts are critical for nearly all aspects of human cognition, from perception tasks like object recognition, to understanding and producing language, to making meaningful actions. Concepts can have two very different kinds of relations: similarity relations based on shared features (e.g., dog – bear), which are called “taxonomic” relations, and contiguity relations based on co-occurrence in events or scenarios (e.g., dog – leash), which are called “thematic” relations. Here we report a systematic rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
172
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(185 citation statements)
references
References 229 publications
(345 reference statements)
11
172
0
2
Order By: Relevance
“…Martin et al, 2016; Tobia and Madan, 2017; see Binkofski and Buxbaum, 2013; for discussion). One possibility is that the relatively low probability of detection of action similarity results from a cognitive bias to rely upon “taxonomic” features such as function and appearance as well as typical “thematic” features such as location (e.g., “kitchen”) and temporal events (e.g., “birthday”) in categorization tasks (see Mirman et al, 2017 for review). The relatively stronger explicit awareness of attributes such as function, appearance, and location as compared to action attributes may be due, in turn, to the benefits and importance of the former in communication, naming, and perhaps “inner speech” (e.g., both bongo drums and oboe can be labeled as instruments; both pillow and comforters can be labeled as bedding).…”
Section: Discussionmentioning
confidence: 99%
“…Martin et al, 2016; Tobia and Madan, 2017; see Binkofski and Buxbaum, 2013; for discussion). One possibility is that the relatively low probability of detection of action similarity results from a cognitive bias to rely upon “taxonomic” features such as function and appearance as well as typical “thematic” features such as location (e.g., “kitchen”) and temporal events (e.g., “birthday”) in categorization tasks (see Mirman et al, 2017 for review). The relatively stronger explicit awareness of attributes such as function, appearance, and location as compared to action attributes may be due, in turn, to the benefits and importance of the former in communication, naming, and perhaps “inner speech” (e.g., both bongo drums and oboe can be labeled as instruments; both pillow and comforters can be labeled as bedding).…”
Section: Discussionmentioning
confidence: 99%
“…The precise role of AG in semantic processing is disputed. Some theories posit that AG acts as a semantic hub coding event-related or thematic semantic knowledge (Binder & Desai, 2011;Mirman, Landrigan, & Britt, 2017;Schwartz et al, 2011). Others have suggested that AG serves as a short-term buffer for recent multimodal experience (Humphreys & Lambon Ralph, 2014).…”
Section: Angular Gyrusmentioning
confidence: 99%
“…umans can describe the potentially infinite features of the world and communicate with others using a finite number of words. To make this possible, our brains need to encode semantics 1 , infer concepts from experiences 2 , relate one concept to another 3,4 , and learn new concepts 5 . Central to these cognitive functions is the brain's semantic system 6 .…”
mentioning
confidence: 99%